Antibacterial Activity of Hydrophobic Composite Materials Containing a Visible-Light-Sensitive Photocatalyst. (28th November 2011) - Yamauchi, Kentaro; Yao, Yanyan; Ochiai, Tsuyoshi; Sakai, Munetoshi; Kubota, Yoshinobu; Yamauchi, Goro
Abstract : The conventional superhydrophobic surface offered by PTFE provides no sterilization performance and is not sufficiently repellent against organic liquids. These limit PTFE's application in the field of disinfection and result a lack of durability. N-doped TiO2 photocatalyst added PTFE composite material was developed to remedy these shortcomings. This paper reports the surface characteristics, and the bactericidal and self-cleaning performance of the newly-developed composite material. The material exhibited a contact angle exceeding 150 degrees consistent with its hydrophobicity despite the inclusion of the hydrophilic N-doped TiO2 . The surface free energy obtained for this composite was 5.8 mN/m. Even when exposed to a weak fluorescent light intensity (100 lx) for 24 hours, the viable cells of gram-negative E. coli on the 12% N-doped TiO2 -PTFE film were reduced 5 logs. The higher bactericidal activity was also confirmed on the gram-positive MRSA. Compared with the N-doped TiO2 coating only, the inactivation rate of the composite material was significantly enhanced. Utilizing the N-doped TiO2 with the PTFE composite coating could successfully remove, by UV illumination, oleic acid adsorbed on its surface. These results demonstrate the potential applicability of the novel N-doped TiO2 photocatalyst hydrophobic composite material for both indoor antibacterial action and outdoor contamination prevention.